Synthesis of Microcrystalline Cellulose from Carpenter Waste and Its Characterizations. Issue 6 (3rd June 2022) - Bhandari, Kunal; Adaval, Akanksha; Bhattacharyya, Arup R.; Maulik, Sankar Roy
ABSTRACT: Carpenter waste has been used as a raw material for synthesizing microcrystalline cellulose through various chemical pre-treatment process sequences. Carpenter waste treated with 10% (w/v) sodium hydroxide followed by various concentration of sodium chlorite (0.5%, 0.7%, and 1.0%) treatment has resulted in substantial loss in weight. The synthesized microcrystalline cellulose has been characterized by different instrumental analysis. FT-IR data showed the successful removal of hemicellulose and lignin from the carpenter waste after various chemical treatments. Wide-angle X-ray diffraction analysis is done to measure the crystallinity index and crystal size of the synthesized microcrystalline cellulose. The microcrystalline cellulose produced under different concentrations of sodium chlorite exhibits crystallinity index in the range of 67.56 to 68.85 and calculated average crystal size within the range of 6.47–6.60 nm. The calculated average particle size of microcrystalline cellulose ranges from 96.42 to 437.83 nm depending on the treatment conditions. Higher concentration of sodium chlorite treatment has led to lowering the particle size. Scanning Electron Microscopic image of microcrystalline cellulose shows curled and soft-flat shaped with rough pits and fibrillated network structure. Field Emission Scanning Electron Microscopic analysis reveals the cylindrical rod-shaped morphology and porous structure of the synthesized microcrystalline cellulose from carpenter waste.